Flexible electrochemical pH sensor as well as preparation method and application thereof
By preparing flexible electrochemical pH sensors with polyaniline sensitive layer on flexible nanofiber substrates, the problems of poor fit and inaccurate measurement of traditional sensors on the skin surface are solved, high sensitivity and accurate pH monitoring are achieved, and the production process is simplified.
Patent Information
- Application Number
- CN202411768768.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
AI Technical Summary
The existing flexible electrochemical pH sensors are constructed on traditional flexible substrates and lack sufficient flexibility and breathability, and cannot fit tightly on the skin surface, resulting in sweat accumulation, inaccurate measurement results, and complex production process.
The working electrode and reference electrode were prepared by flexible nanofiber substrate and stencil printing method, and a polyaniline sensitive layer was deposited on the working electrode, and the sensor's sensitivity and monitoring accuracy were improved by electrospinning technology and cyclic voltammetry.
It realizes the high sensitivity, good flexibility and breathable moisture permeability of flexible electrochemical pH sensors, and can be closely attached to the skin surface to accurately monitor the pH value of body fluids, improves measurement accuracy, and simplifies the production process.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, in particular to a flexible electrochemical pH sensor and a preparation method and application thereof. Background Art
[0002] Electrochemical pH sensors can accurately measure the pH value of a solution. Various physiological processes of the human body require the maintenance of a specific acid-base balance. Therefore, electrochemical pH sensors are often used to detect the pH of human sweat or other body fluids to assess the acid-base balance in the human body and further assess the health of the human body.
[0003] At present, most of the existing flexible electrochemical pH sensors are constructed on traditional flexible substrates, such as polyethylene terephthalate (PET), polyimide (PI), polydimethylsiloxane (PDMS), polyurethane (PU) and polymethyl methacrylate (PMMA). These polymer films are usually not breathable, lack sufficient flexibility, and cannot fit tightly on the skin surface, which causes the gap between them and the epidermis to cause sweat accumulation and make the test results inaccurate. At the same time, this will also affect the comfort of the wearer, greatly shortening the working time of the sensor on the skin. In addition, the process of processing pH sensors on such substrates is usually complicated and the production process is cumbersome. Summary of the invention
[0004] Based on this, it is necessary to provide a flexible electrochemical pH sensor and its preparation method and application to address the above problems. The flexible electrochemical pH sensor has the characteristics of high sensitivity, good flexibility, good air permeability and moisture permeability, can be closely attached to the skin surface to monitor the pH value of body fluids, and has high monitoring accuracy, and the preparation method is simple.
[0005] A flexible electrochemical pH sensor comprises a flexible nanofiber substrate and a working electrode and a reference electrode arranged at intervals on the surface of the flexible nanofiber substrate, wherein the working electrode comprises a first working part and a first wire part connected to the first working part, and the first working part is provided with a polyaniline sensitive layer.
[0006] In one embodiment, the thickness of the flexible nanofiber substrate is 40 μm-90 μm;
[0007] And / or, the thickness of the polyaniline sensitive layer is 6 μm-10 μm.
[0008] In one embodiment, the air permeability of the flexible nanofiber substrate is 60.5 mm / s-93.2 mm / s, and the moisture permeability is 2796.8 g / m 2 24h-2976.7g / m2 24h;
[0009] And / or, the flexible nanofiber substrate is selected from a thermoplastic polyurethane nanofiber substrate or a styrene-butadiene-styrene block copolymer nanofiber substrate.
[0010] In one embodiment, the reference electrode includes a second working part and a second wire part connected to the second working part, the second working part is provided with a protective layer, the thickness of the protective layer is 7μm-10μm, and the protective layer contains polyvinyl butyral, sodium chloride and carbon nanotubes.
[0011] In one embodiment, the working electrode is a graphene working electrode, and the reference electrode is a silver / silver chloride reference electrode.
[0012] A method for preparing the flexible electrochemical pH sensor as described above comprises the following steps:
[0013] The flexible nanofiber substrate was prepared by electrospinning technology;
[0014] The reference electrode and working electrode were prepared on the surface of the flexible nanofiber substrate by template printing;
[0015] The polyaniline sensitive layer was deposited on the first working part of the working electrode by cyclic voltammetry to obtain a flexible electrochemical pH sensor.
[0016] In one embodiment, the steps of preparing a reference electrode and a working electrode on a flexible nanofiber substrate by template printing are as follows:
[0017] Two conductive wires were printed on the surface of a flexible nanofiber substrate using a template printing method;
[0018] The working electrode slurry is printed on one end of a wire by a template printing method to form a working electrode, and the reference electrode slurry is printed on one end of another wire to form a reference electrode.
[0019] In one embodiment, in the step of preparing the reference electrode and the working electrode on the flexible nanofiber substrate by template printing, at least one of the following conditions is also met:
[0020] (1) The material of the wire is selected from at least one of gold, graphite, graphene, carbon nanotubes, platinum, palladium, and silver;
[0021] (2) The working electrode slurry is selected from graphene slurry, and the reference electrode slurry is selected from silver / silver chloride slurry.
[0022] In one embodiment, the method for preparing the flexible electrochemical pH sensor further satisfies at least one of the following conditions:
[0023] (1) In the step of preparing the flexible nanofiber substrate by electrospinning technology, the electrospinning parameters include: an applied positive voltage of 10 kV-20 kV, an applied negative voltage of -1 kV to -5 kV, a drum speed of 400 rpm-600 rpm, a liquid supply rate of 0.02 mL / min-0.1 mL / min, a distance between the needle and the collecting device of 10 cm-20 cm, a temperature of 25° C.-35° C., and an ambient relative humidity of 35%-45%;
[0024] (2) In the step of preparing the flexible nanofiber substrate by electrospinning technology, the mass volume ratio of the spinning solution used is 18%-26%, and the spinning solution is selected from a thermoplastic polyurethane solution and / or a styrene-butadiene-styrene block copolymer solution;
[0025] (3) in the step of depositing the polyaniline sensitive layer on the first working part of the working electrode by cyclic voltammetry, using aniline solution as a raw material, and depositing the polyaniline sensitive layer on the first working part of the working electrode by cyclic voltammetry, wherein the concentration of aniline in the aniline solution is 0.1 mol / L-0.3 mol / L;
[0026] (4) It also includes placing a protective layer precursor solution in the second working part of the reference electrode and forming a protective layer after drying, wherein the protective layer precursor solution includes polyvinyl butyral, sodium chloride, carbon nanotubes and an alcohol solvent, wherein the mass ratio of the polyvinyl butyral to the sodium chloride is 1.4:1-1.7:1, and the mass ratio of the polyvinyl butyral to the carbon nanotubes is 100:1-50:1.
[0027] The flexible electrochemical pH sensor as described above is used for monitoring pH in body fluids.
[0028] In the flexible electrochemical pH sensor of the present invention, a flexible nanofiber substrate is used, so that the flexible electrochemical pH sensor has good flexibility, air permeability and moisture permeability, can be closely attached to the skin surface to monitor the pH value of body fluids, and improve the sensitivity and monitoring accuracy of the flexible electrochemical pH sensor; at the same time, by setting a polyaniline sensitive layer in the first working part of the working electrode, polyaniline will undergo redox reaction under different pH values, so that the flexible electrochemical pH sensor responds quickly under the pH environment, quickly realizes the measurement of pH value, and improves the measurement accuracy. Therefore, the flexible electrochemical pH sensor of the present invention has the characteristics of high sensitivity, good flexibility, good air permeability and moisture permeability, can be closely attached to the skin surface to monitor the pH value of body fluids, and has high monitoring accuracy, and the manufacturing method is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a structural exploded view of the flexible electrochemical pH sensor in Example 1 of the present invention;
[0031] Figure 2 for Figure 1 Electron microscopy image of the medium-flexible nanofiber substrate;
[0032] Figure 3 The graphs of the conductor printing template, the working electrode printing template and the reference electrode printing template in Example 1 of the present invention, wherein A represents the graph of the conductor printing template, B represents the graph of the working electrode printing template, and C represents the graph of the reference electrode printing template;
[0033] Figure 4 This is a voltage test diagram of the flexible electrochemical pH sensor of Example 1 of the present invention at different pH values;
[0034] Figure 5 This is a comparison diagram of the sensing of artificial sweat of three pH values by the flexible electrochemical pH sensor of Example 1 of the present invention and the sensing of artificial sweat of three pH values by a commercial pH sensor, wherein in the figure, E represents the flexible electrochemical pH sensor of Example 1, F represents the commercial pH sensor, pH1 represents the pH test value, and pH2 represents the pH standard value;
[0035] Figure 6 This is a monitoring change diagram of the pH value in skin sweat at different times by the flexible electrochemical pH sensor of Example 1 of the present invention.
[0036] Figure numerals: 1. flexible nanofiber substrate; 2. first working part; 3. first conductor part; 4. polyaniline sensitive layer; 5. second working part; 6. second conductor part; 7. protective layer. DETAILED DESCRIPTION
[0037] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0039] like Figure 1 As shown, a flexible electrochemical pH sensor according to an embodiment of the present invention comprises a flexible nanofiber substrate 1 and a working electrode and a reference electrode spaced apart on the surface of the flexible nanofiber substrate 1, wherein the working electrode comprises a first working portion 2 and a first wire portion 3 connected to the first working portion 2, wherein the first wire portion 3 is used to connect to an external circuit.
[0040] The first working part 2 is provided with the polyaniline sensitive layer 4 .
[0041] In the present invention, the flexible nanofiber substrate 1 has the characteristics of good flexibility, air permeability and moisture permeability, and a flexible nanofiber substrate is used as a substrate, so that the flexible electrochemical pH sensor has good flexibility, air permeability and moisture permeability, can be closely attached to the skin surface to monitor the pH value of body fluids, and improves the sensitivity and monitoring accuracy of the flexible electrochemical pH sensor.
[0042] At the same time, by setting the polyaniline sensitive layer 4 as the sensitive membrane of the working electrode in the first working part 2 of the working electrode, the polyaniline undergoes redox reaction at different pH values. Specifically, in an acidic environment, the polyaniline absorbs H + , resulting in the protonation of the nitrogen atom site, thus causing a change in potential; in an alkaline environment, the H absorbed by polyaniline + The process of being neutralized and deprotonated makes the flexible electrochemical pH sensor respond quickly in the pH environment, quickly realizes the measurement of pH value, and improves the measurement accuracy. Specifically, the flexible electrochemical pH sensor of the present invention can sense in the range of pH 2-10, and the sensitivity is above 66.28mV / Ph.
[0043] Therefore, the flexible electrochemical pH sensor of the present invention has the characteristics of high sensitivity, good flexibility, and good air and moisture permeability. It can be closely attached to the skin surface to monitor the pH value of body fluids, and has high monitoring accuracy. At the same time, the manufacturing method is simple.
[0044] It can be understood that the working principle of the flexible electrochemical pH sensor in the present invention is based on the different electrical properties of the polyaniline sensitive layer 4 deposited on the working electrode for different hydrogen ion concentrations to achieve monitoring of pH.
[0045] Specifically, combined Figure 1 As shown, the working electrode and the reference electrode are arranged in parallel and at intervals on the surface of the flexible nanofiber substrate 1, and the two do not contact each other. Furthermore, the working electrode and the reference electrode are arranged in parallel.
[0046] Optionally, the thickness of the flexible nanofiber substrate 1 is 40 μm-90 μm. It is understood that the thickness of the flexible nanofiber substrate 1 includes but is not limited to 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, and 90 μm. In this way, by controlling the thickness of the flexible nanofiber substrate 1, the flexibility, air permeability, and moisture permeability of the flexible electrochemical pH sensor can be better regulated while ensuring the overall structural strength of the flexible electrochemical pH sensor.
[0047] Optionally, the air permeability of the flexible nanofiber substrate 1 is 60.5 mm / s-93.2 mm / s, and the moisture permeability is 2796.8 g / m 2 24h-2976.7g / m 2 ·24h. Such a setting can further improve the overall air permeability and moisture permeability of the flexible electrochemical pH sensor.
[0048] Furthermore, the flexible nanofiber substrate 1 is selected from a thermoplastic polyurethane nanofiber substrate or a styrene-butadiene-styrene block copolymer nanofiber substrate, preferably a thermoplastic polyurethane nanofiber substrate. This arrangement can further improve the overall flexibility, air permeability and moisture permeability of the flexible electrochemical pH sensor.
[0049] Optionally, the thickness of the polyaniline sensitive layer 4 is 6 μm-10 μm; it is understood that the thickness of the polyaniline sensitive layer 4 includes but is not limited to 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm. Such a configuration is conducive to further improving the sensitivity and monitoring accuracy of the flexible electrochemical pH sensor.
[0050] Combination Figure 1As shown, the reference electrode comprises a second working portion 5 and a second wire portion 6 connected to the second working portion 5, the second working portion 5 is provided with a protective layer 7, and the second wire portion 6 is used to connect to an external circuit, specifically, the first working portion 2 and the second working portion 5 are located on the same side. Such a configuration is conducive to improving the reference electrode from being oxidized when immersed in a solution, thereby improving the stability of the reference potential, and thereby improving the monitoring accuracy of the flexible electrochemical pH sensor.
[0051] Furthermore, the thickness of the protective layer 7 is 7 μm-10 μm. Such a configuration is beneficial to further improve the oxidation resistance of the reference electrode, improve the working stability and service life.
[0052] In the present invention, the protective layer 7 contains polyvinyl butyral and sodium chloride. This configuration is beneficial to improving the anti-interference ability of the reference electrode and better ensuring that the reference electrode maintains a stable potential during operation.
[0053] Furthermore, the protective layer 7 also contains carbon nanotubes. Such a configuration is conducive to improving the conductivity of the reference electrode, so that when the flexible electrochemical pH sensor is just immersed in the solution to be tested and the ion exchange in the reference electrode is not complete, it provides stable conductive support.
[0054] Therefore, in the present invention, it is preferred that the protective layer 7 contains polyvinyl butyral, sodium chloride and carbon nanotubes.
[0055] Optionally, the working electrode is a graphene working electrode, and the reference electrode is a silver / silver chloride reference electrode.
[0056] It can be understood that in the present invention, when the working electrode is a graphene working electrode, the first working part 2 of the working electrode includes a graphene layer provided on the surface of the flexible nanofiber substrate 1 and a polyaniline sensitive layer 4 provided on the surface of the graphene layer; similarly, when the reference electrode is a silver / silver chloride reference electrode, the second working part 5 of the reference electrode includes a silver / silver chloride layer provided on the surface of the flexible nanofiber substrate 1, or the second working part 5 of the reference electrode includes a silver / silver chloride layer provided on the surface of the flexible nanofiber substrate 1 and a protective layer 7 provided on the surface of the silver / silver chloride layer.
[0057] At the same time, the present invention also provides a method for preparing the flexible electrochemical pH sensor as described above, comprising the following steps:
[0058] S1, preparing a flexible nanofiber substrate 1 by electrospinning technology;
[0059] S2, preparing a reference electrode and a working electrode on the surface of the flexible nanofiber substrate 1 by a template printing method;
[0060] S3, depositing a polyaniline sensitive layer 4 on the first working part 2 of the working electrode by cyclic voltammetry to obtain a flexible electrochemical pH sensor.
[0061] In the present invention, a flexible nanofiber substrate 1 is prepared by adopting electrospinning technology, and a reference electrode and a working electrode are prepared on the surface of the flexible nanofiber substrate 1 by using a template printing method; and a polyaniline sensitive layer 4 is deposited on the surface of the working electrode by using cyclic voltammetry, so as to obtain a flexible electrochemical pH sensor with high sensitivity, good flexibility, and good air and moisture permeability. Moreover, compared with the traditional preparation method, the preparation method is simple in process.
[0062] In step S1, the spinning solution is spun using electrospinning technology to form a flexible nanofiber substrate 1.
[0063] Specifically, first provide a spinning solution; then suck the spinning solution into a 10mL screw-mouth syringe, use a 19G stainless steel dispensing needle as the syringe needle, and load the syringe onto the injection pump in the electrospinning machine; stick the release paper to the surface of the drum in the electrospinning machine, set the distance between the syringe needle and the drum, and connect the positive voltage and negative voltage terminal terminals of the electrospinning machine to the bottom of the dispensing needle and the drum respectively; set various parameters for electrospinning, start the electrospinning machine for spinning, and obtain a flexible nanofiber substrate 1.
[0064] Optionally, the electrospinning parameters include: an applied positive voltage of 10kV-20kV, an applied negative voltage of -1kV to -5kV, a drum speed of 400rpm-600rpm, a liquid supply rate of 0.02mL / min-0.1mL / min, a distance between the needle and the collecting device of 10cm-20cm, a temperature of 25℃-35℃, and an ambient relative humidity of 35%-45%. Such an arrangement is conducive to spinning to form a flexible nanofiber substrate 1 that is breathable, moisture-permeable, and has good flexibility.
[0065] In one embodiment, the electrospinning time is 30 min-45 min, preferably 35 min. Such a setting is conducive to controlling the thickness of the flexible nanofiber substrate 1.
[0066] Optionally, the mass volume ratio of the spinning solution is 18%-26%. Such a setting is conducive to forming a better spinning effect.
[0067] Specifically, the spinning solution is mixed with a high molecular polymer and an organic solvent, and then stirred evenly at room temperature to obtain a spinning solution, wherein the stirring rate is 300 rpm-500 rpm, preferably 400 rpm, and the stirring time is 3h-5h, preferably 4h. It can be understood that the mass volume ratio of the high molecular polymer to the organic solvent is 18%-26%.
[0068] In one embodiment, the high molecular polymer is selected from thermoplastic polyurethane solution and / or styrene-butadiene-styrene block copolymer; the organic solvent is selected from at least one of N,N-dimethylformamide, tetrahydrofuran and dichloromethane.
[0069] In the present invention, the spinning solution is selected from at least one of a thermoplastic polyurethane solution and a styrene-butadiene-styrene block copolymer solution, preferably a thermoplastic polyurethane solution. This arrangement is conducive to improving the flexibility of the flexible nanofiber substrate 1.
[0070] Specifically, when the spinning solution is selected from a thermoplastic polyurethane solution, the organic solvent is preferably a mixed solvent of tetrahydrofuran and N,N-dimethylformamide, wherein the volume ratio of tetrahydrofuran to N,N-dimethylformamide is 1:1, and the mass volume ratio of the thermoplastic polyurethane to the mixed solvent is preferably 25%.
[0071] In step S2, the steps of preparing the reference electrode and the working electrode on the flexible nanofiber substrate 1 by template printing are as follows:
[0072] S21, printing two conductors on the surface of the flexible nanofiber substrate 1 by using a template printing method;
[0073] S22, using a template printing method to print the working electrode slurry on one end of a wire to form a working electrode, and printing the reference electrode slurry on one end of another wire to form a reference electrode. It can be understood that in this step, the printing area of the working electrode is the first working part 2 of the working electrode, and the printing area of the reference electrode is the second working part 5 of the reference electrode. Specifically, the working electrode slurry is printed on one end of a wire using a template printing method to form the first working part 2 and the first wire part 3 of the working electrode, and the reference electrode slurry is printed on one end of another wire to form the second working part 5 and the second wire part 6 of the reference electrode, thereby obtaining a working electrode and a reference electrode.
[0074] In step S21, the conductor slurry is used to print two conductors on the surface of the flexible nanofiber substrate 1 by a template printing method, wherein the material of the conductor is selected from at least one of gold, graphite, graphene, carbon nanotubes, platinum, palladium, and silver, preferably gold. Such a setting is conducive to improving the printing effect, and at the same time is conducive to improving the flexibility and stretchability of the conductor, thereby improving the working stability of the flexible electrochemical pH sensor.
[0075] It can be understood that the wire paste is selected from at least one of gold paste, graphite paste, graphene paste, carbon nanotube paste, platinum paste, and silver paste, preferably gold paste.
[0076] Specifically, first draw the cutting pattern in the CAD software and save it in DXF format; then import the DXF file into the laser cutting machine software and set the cutting parameters; use a PET film with a thickness of 0.05 mm as a raw material, use a laser cutting machine to cut the specified pattern, and obtain a template for wire printing; use the template for wire printing and the wire slurry as a raw material to print the corresponding two wires on the surface of the flexible nanofiber substrate 1 prepared in step S1, and then place it at 80°C-120°C for drying for 0.8h-1.2h.
[0077] In step S22, referring to the preparation method of the template for printing the above-mentioned conductor, according to the preset pattern, the corresponding template for printing the working electrode and the template for printing the reference electrode are prepared respectively, and then the template for printing the working electrode is used, and the working electrode slurry is used as the raw material to print the working electrode slurry at one end of a conductor, and then it is placed at 70℃-90℃ and dried for 15min-25min to form the first working part 2 of the working electrode, and the working electrode is obtained; the template for printing the reference electrode is used, and the reference electrode slurry is used as the raw material to print the reference electrode slurry at one end of the other conductor, and then it is placed at 70℃-90℃ and dried for 15min-25min to form the second working part 5 of the reference electrode, and the reference electrode is obtained.
[0078] Furthermore, the working electrode slurry is selected from graphene slurry, and the reference electrode slurry is selected from silver / silver chloride slurry.
[0079] In step S3, a polyaniline sensitive layer 4 is deposited on the first working part 2 of the working electrode using cyclic voltammetry using aniline solution as a raw material, wherein the concentration of aniline in the aniline solution is 0.1 mol / L-0.3 mol / L, preferably 0.1 mol / L.
[0080] In one embodiment, the aniline solution is obtained by mixing aniline and dilute hydrochloric acid, wherein the concentration of the dilute hydrochloric acid is 0.3 mol / L-1 mol / L, preferably 1 mol / L.
[0081] Specifically, the specific steps of depositing the polyaniline sensitive layer 4 on the first working part 2 of the working electrode by cyclic voltammetry are as follows: first, a 3 mm thick acrylic plate is used as the raw material, and a laser cutting machine is used to cut out a bracket for placing the flexible nanofiber substrate 1 and the counter electrode; then the flexible nanofiber substrate 1 with the working electrode and the reference electrode and the platinum counter electrode are respectively attached to the corresponding two brackets; the working electrode slurry is used to connect the first wire part 3 of the working electrode with the external wire to achieve conductive connection; the commercial wire is welded to the surface of the platinum electrode with solder, and a layer of silicone is applied and cured at the welding point for protection; then the above-mentioned bracket is placed in a beaker, and the flexible nanofiber substrate 1 with the working electrode and the reference electrode is placed on the opposite side of the platinum sheet, with a spacing of about 10 mm; the first wire part 3 of the working electrode is connected to the reference electrode. The second wire portion 6 of the electrode is respectively connected to the working electrode and the reference electrode of the electrochemical workstation, and the wire led out of the platinum counter electrode is connected to the counter electrode on the electrochemical workstation; 0.5M dilute hydrochloric acid is added to the beaker until the electrode position is completely immersed, and the working electrode is cleaned by cyclic voltammetry, and the cyclic voltammetry parameters are set, wherein the voltage is -0.1V to 0.9V, the scan rate is 0.1V / s, and the number of cycles is 10. Then, the solution in the beaker is replaced with an aniline solution, and polyaniline is deposited on the working electrode by cyclic voltammetry to form a polyaniline sensitive layer 4, and the cyclic voltammetry parameters are set, wherein the voltage range is -0.2V to 1V, the scan rate is 0.1V / s, and the number of cycles is 25. Finally, the working electrode and the reference electrode are taken out, and the working electrode and the reference electrode are cleaned with distilled water. After drying at room temperature, a flexible electrochemical pH sensor is obtained.
[0082] Optionally, the method for preparing the flexible electrochemical pH sensor further comprises: placing a protective layer precursor solution on the second working portion 5 of the reference electrode, and forming a protective layer 7 through drying.
[0083] The protective layer precursor solution includes polyvinyl butyral, sodium chloride and an alcohol solvent, wherein the mass ratio of the polyvinyl butyral to the sodium chloride is 1.4:1-1.7:1.
[0084] Furthermore, the protective layer precursor solution also includes carbon nanotubes, wherein the mass ratio of the polyvinyl butyral to the carbon nanotubes is 100:1-50:1.
[0085] Specifically, the protective layer precursor solution is prepared by dissolving polyvinyl butyral, sodium chloride and carbon nanotubes in an alcohol solvent and subjecting the solution to ultrasonic oscillation, wherein the alcohol solvent is preferably methanol.
[0086] In one embodiment, the protective layer precursor solution is sucked with a pipette and then drop-coated on the second working portion 5 of the reference electrode, and dried at room temperature for 4h-6h to form a protective layer 7 to obtain a flexible electrochemical pH sensor.
[0087] It should be noted that, in the present invention, the step of placing the protective layer precursor solution in the second working part 5 of the reference electrode and forming the protective layer 7 by drying is performed after step S2 and before step S3.
[0088] In addition, the present invention also provides a flexible electrochemical pH sensor as described above for monitoring pH in body fluids. This application has good application prospects in the field of wearable device health monitoring.
[0089] In one embodiment, the body fluid is selected from any one of skin sweat and saliva.
[0090] The flexible electrochemical pH sensor and its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0091] Example 1
[0092] 7.5 g of thermoplastic polyurethane, 15 mL of N,N-dimethylformamide and 15 mL of tetrahydrofuran were added into a beaker and stirred evenly at room temperature using a magnetic stirrer, wherein the speed of the magnetic stirrer was 400 rpm and the stirring time was 4 h to obtain a thermoplastic polyurethane spinning solution; 78.1 mg of polyvinyl butyral, 50 mg of sodium chloride and 1.2 mg of carbon nanotubes were dissolved in 1 mL of methanol and ultrasonically oscillated for 1 hour to obtain a protective layer precursor solution; aniline and 1 M dilute hydrochloric acid were mixed to obtain a 0.1 M aniline solution.
[0093] Two 10mL screw-mouth syringes were used to absorb the thermoplastic polyurethane spinning solution obtained above, and a stainless steel dispensing needle (19G) was installed on the screw-mouth syringe; then the two screw-mouth syringes were fixed on the injection pump in the electrospinning machine (TEADFS-100, Beijing Xinrui Baina Technology Co., Ltd.), and the positive voltage interface of the electrospinning machine was fixed to the bottom of the stainless steel dispensing needle; a layer of release paper was pasted on the drum in the electrospinning machine as an electrospinning collector, and the position of the injection pump was adjusted so that the distance from the stainless steel dispensing needle to the drum was 15cm; finally, the working parameters of the electrospinning machine were set, wherein the external positive voltage was 11Kv, the external negative voltage was -5kV, the liquid supply rate was 0.06mL / min, the drum speed was 600rpm, the temperature was 30°C, the ambient relative humidity was 40%, and the electrospinning machine was started and operated for 40min, and then the electrospinning machine was turned off to obtain a flexible nanofiber substrate with a thickness of 65μm.
[0094] Draw the following in CAD software: Figure 3 The wire printing template, working electrode printing template and reference electrode printing template shown in the figure are saved in the corresponding DXF format; the corresponding DXF file is imported into the laser cutting machine software and the cutting parameters are set, and a 0.05 mm thick PET film is used as a raw material to prepare the corresponding wire printing template, working electrode printing template and reference electrode printing template respectively; then the wire printing template obtained above is placed on the surface of the flexible nanofiber substrate, and two gold wires are printed on the surface of the flexible nanofiber substrate using conductive gold paste as a raw material; then it is placed on a constant temperature heating table and heated and dried at 100°C for 1 hour.
[0095] A working electrode printing template was placed on the surface of one of the gold wires, and then a layer of graphene slurry was printed on one end of the gold wire, and then the template was placed on a constant temperature heating table and heated and dried at 80°C for 20 minutes to form a first working part and a first wire part, thereby obtaining a working electrode; then, a reference electrode printing template was placed on the surface of another gold wire, and then a layer of silver / silver chloride slurry was printed on one end of the gold wire so that the graphene slurry and the silver / silver chloride slurry were located on the same side, and then the template was placed on a constant temperature heating table and heated and dried at 80°C for 20 minutes to form a second working part and a second wire part, thereby obtaining a reference electrode; 5 μL of the protective layer precursor solution obtained above was taken with a pipette, and then drop-coated on the second working part of the reference electrode, and dried at room temperature for 5 hours to form a protective layer with a thickness of 8 μm.
[0096] A 3 mm thick acrylic plate was used as a raw material, and a laser cutting machine was used to cut out a bracket for placing a flexible nanofiber substrate and a counter electrode; then the flexible nanofiber substrate with a working electrode and a reference electrode and a platinum counter electrode were attached to the corresponding two brackets respectively; silver paste was used to connect the first wire part of the working electrode with the commercial wire, and the commercial wire was welded to the surface of the platinum electrode using solder, and a layer of silicone was applied and cured at the welding point for protection; then the above bracket was placed in a beaker, and the flexible nanofiber substrate with a working electrode and a reference electrode was placed on the opposite side of the platinum sheet with an interval of about 10 mm; the first wire part and the second wire part corresponding to the working electrode and the reference electrode were connected to the working electrode and the reference electrode of the electrochemical workstation respectively, and the wire led out of the platinum counter electrode was connected to the counter electrode on the electrochemical workstation; 0.5 M dilute hydrochloric acid was added to the beaker until the electrode position was completely immersed, and the working electrode was cleaned using cyclic voltammetry, and the cyclic voltammetry parameters were set, wherein the voltage was -0.1 V to 0.9 V, the scan rate was 0.1 V / s, and the number of cycles was 10.
[0097] Subsequently, the solution in the beaker was replaced with the aniline solution obtained above, and polyaniline was deposited on the first working part of the working electrode using cyclic voltammetry to form a polyaniline sensitive layer with a thickness of 8 μm. The cyclic voltammetry parameters were set, wherein the voltage range was -0.2 V to 1 V, the scan rate was 0.1 V / s, and the number of cycles was 25. After the deposition was completed, the working electrode and the reference electrode were taken out, and the working electrode and the reference electrode were washed with distilled water. After drying at room temperature, the following was obtained: Figure 1 The flexible electrochemical pH sensor shown.
[0098] At the same time, the flexible nanofiber substrate in this embodiment was tested using an electron microscope, and the test results are as follows: Figure 2 As shown, from Figure 2 It can be seen that the flexible nanofiber substrate is a porous structure, so the flexible nanofiber substrate can provide good flexibility, air permeability, and moisture permeability. At the same time, the air permeability of the flexible nanofiber substrate in this embodiment was tested according to the national standard GB / T5453-1997100Pa, and the moisture permeability of the flexible nanofiber substrate in this embodiment was tested according to the national standard GB / T12704.2-2009 condition A. Among them, the air permeability of the flexible nanofiber substrate is 70.5mm / s, and the moisture permeability is 2890g / m 2 ·24h.
[0099] Example 2
[0100] Example 2 is different from Example 1 only in that, in the step of preparing the flexible nanofiber substrate by electrospinning technology, the electrospinning parameters include: the external positive voltage is 10 kV, the external negative voltage is -2 kV, the rotation speed of the drum is 450 rpm, the liquid supply rate is 0.06 mL / min, the distance between the needle and the collecting device is 12 cm, the temperature is 30 ° C, the relative humidity of the environment is 40%, and the electrospinning machine is operated for 30 min; 6 μL of the protective layer precursor obtained above is sucked by a pipette The solution is then drop-coated on the second working part of the reference electrode, and dried at room temperature for 5 hours to form a protective layer; in the step of depositing polyaniline on the first working part of the working electrode to form a polyaniline sensitive layer using cyclic voltammetry, the voltage range is -0.3V to 1.2V, the scan rate is 0.1V / s, the number of cycles is 30, and the other conditions are the same to obtain a flexible electrochemical pH sensor, wherein the thickness of the flexible nanofiber substrate is 40μm, the air permeability is 93.2mm / s, and the moisture permeability is 2976.7g / m 2 After 24 hours, the thickness of the protective layer is 9 μm, and the thickness of the polyaniline sensitive layer is 7 μm.
[0101] Example 3
[0102] Example 3 is different from Example 1 only in that, in the step of preparing the flexible nanofiber substrate by electrospinning technology, the electrospinning parameters include: the external positive voltage is 18 kV, the external negative voltage is -5 kV, the rotation speed of the drum is 600 rpm, the liquid supply rate is 0.08 mL / min, the distance between the needle and the collecting device is 18 cm, the temperature is 30 ° C, the relative humidity of the environment is 35%, and the electrospinning machine is operated for 45 min; 4 μL of the protective layer precursor obtained above is sucked by a pipette The solution is then drop-coated on the second working part of the reference electrode, and dried at room temperature for 5 hours to form a protective layer; in the step of depositing polyaniline on the first working part of the working electrode to form a polyaniline sensitive layer using cyclic voltammetry, the voltage range is -0.2V to 1.1V, the scan rate is 0.1V / s, the number of cycles is 28, and the other conditions are the same to obtain a flexible electrochemical pH sensor, wherein the thickness of the flexible nanofiber substrate is 85μm, the air permeability is 63.5mm / s, and the moisture permeability is 2820g / m 2 After 24 hours, the thickness of the protective layer is 7 μm, and the thickness of the polyaniline sensitive layer is 8 μm.
[0103] The voltage of the flexible electrochemical pH sensor prepared in Example 1 was tested at different pH values. The test results are as follows: Figure 5 As shown, the specific test method is as follows: First, prepare buffer solutions with pH values of 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, and 10.0. Specifically, 9.47 g of disodium hydrogen phosphate and 9.08 g of potassium dihydrogen phosphate are dissolved in 1000 ml of deionized water to prepare two mother solutions for standby use; then 10 ml of the two mother solutions are respectively extracted and mixed, and the pH values are measured using a commercial pH sensor, and the two mother solutions are added according to the measured values, and 1 M hydrochloric acid or 1 M sodium hydroxide is added dropwise, and the pH of the buffer solution is adjusted to the target value by adding and measuring at the same time.
[0104] At the same time, the flexible electrochemical pH sensor in Example 1 is attached to the acrylic plate bracket, and then the bracket is placed in a beaker, and the prepared PBS buffer solutions of different pH values are poured into the beaker; the first wire part of the working electrode and the second wire part of the reference electrode in the flexible electrochemical pH sensor are respectively connected to the corresponding electrodes of the electrochemical workstation; then the electrochemical workstation is set to the open circuit voltage mode to test the prepared flexible electrochemical pH sensor, and the test time is set to 120s, and the stable data of the last 30s is taken for analysis. According to the pH value of the solution being tested and the voltage data at the time of stability, a relationship curve between the output voltage and the pH value when the sensor is working is established, and the curve is fitted to obtain the relationship formula as shown in formula (1): y = -66.28x + 416.65, where x is the pH value, such as Figure 4 As shown. Figure 4It can be seen that the flexible electrochemical pH sensor of the present invention has a sensitivity of 66.28 mV / pH in the pH range of 2-10, indicating that the flexible electrochemical pH sensor of the present invention can achieve linear voltage response to different pH values and has high sensitivity.
[0105] The pH value of the flexible electrochemical pH sensor prepared in Example 1 was tested in artificial sweat (the artificial sweat was purchased from Shenzhen Kejingda Instrument Equipment Co., Ltd.). The test results are as follows: Figure 5 As shown, the specific test method is as follows: the flexible electrochemical pH sensor in Example 1 is placed in artificial sweat solutions with pH values of 4.7, 6.5 and 8.8 to perform an open circuit voltage test, and the test is repeated three times; then the tested open circuit voltage value is converted into a pH value according to the above formula (1), and the result is compared with the test result of a commercial pH meter. Figure 5 It can be seen that the sensing results of the flexible electrochemical pH sensor of the present invention for artificial sweat of three pH values are very close to the measurement results of the commercial pH sensor, indicating that the flexible electrochemical pH sensor of the present invention has a good application prospect in sweat pH measurement.
[0106] In addition, the monitoring results of the flexible electrochemical pH sensor prepared in Example 1 on skin sweat sensing are as follows: Figure 6 As shown, the specific test method is as follows: the flexible electrochemical pH sensor in Example 1 is attached to the surface of human skin after sweating during exercise, the electrode wire of the flexible electrochemical sensor is connected to the electrochemical workstation, and the open circuit voltage method is used for detection, and the tested open circuit voltage value is converted into a pH value according to the above formula (1). Figure 6 It can be seen that the flexible electrochemical pH sensor of the present invention can be conformally attached to the surface of human skin, and the pH value of sweat on human skin can be stably and reliably monitored.
[0107] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0108] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A flexible electrochemical pH sensor, characterized in that: The flexible electrochemical pH sensor includes a flexible nanofiber substrate and a working electrode and a reference electrode spaced apart on the surface of the flexible nanofiber substrate, wherein the working electrode includes a first working part and a first wire part connected to the first working part, and the first working part is provided with a polyaniline sensitive layer.
2. The flexible electrochemical pH sensor according to claim 1, characterized in that: The thickness of the flexible nanofiber substrate is 40 μm-90 μm; And / or, the thickness of the polyaniline sensitive layer is 6 μm-10 μm.
3. The flexible electrochemical pH sensor according to claim 1, characterized in that: The air permeability of the flexible nanofiber substrate is 60.5 mm / s-93.2 mm / s, and the moisture permeability is 2796.8 g / m 2 24h-2976.7g / m 2 24h; And / or, the flexible nanofiber substrate is selected from a thermoplastic polyurethane nanofiber substrate or a styrene-butadiene-styrene block copolymer nanofiber substrate.
4. The flexible electrochemical pH sensor according to claim 1, characterized in that: The reference electrode comprises a second working part and a second wire part connected to the second working part. The second working part is provided with a protective layer. The thickness of the protective layer is 7 μm-10 μm. The protective layer contains polyvinyl butyral, sodium chloride and carbon nanotubes.
5. The flexible electrochemical pH sensor according to any one of claims 1 to 4, characterized in that: The working electrode is a graphene working electrode, and the reference electrode is a silver / silver chloride reference electrode.
6. A method for preparing a flexible electrochemical pH sensor according to any one of claims 1 to 5, characterized in that: The steps include: The flexible nanofiber substrate was prepared by electrospinning technology; The reference electrode and working electrode were prepared on the surface of the flexible nanofiber substrate by template printing; The polyaniline sensitive layer was deposited on the first working part of the working electrode by cyclic voltammetry to obtain a flexible electrochemical pH sensor.
7. The method for preparing a flexible electrochemical pH sensor according to claim 6, characterized in that: The steps of preparing the reference electrode and the working electrode on the flexible nanofiber substrate by template printing are as follows: Two conductive wires were printed on the surface of a flexible nanofiber substrate using a template printing method; The working electrode slurry is printed on one end of a wire by a template printing method to form a working electrode, and the reference electrode slurry is printed on one end of another wire to form a reference electrode.
8. The method for preparing a flexible electrochemical pH sensor according to claim 7, characterized in that: In the step of preparing the reference electrode and the working electrode on the flexible nanofiber substrate by template printing, at least one of the following conditions is also met: (1) The material of the wire is selected from at least one of gold, graphite, graphene, carbon nanotubes, platinum, palladium, and silver; (2) The working electrode slurry is selected from graphene slurry, and the reference electrode slurry is selected from silver / silver chloride slurry.
9. The method for preparing a flexible electrochemical pH sensor according to claim 6, characterized in that: The method for preparing the flexible electrochemical pH sensor further satisfies at least one of the following conditions: (1) In the step of preparing the flexible nanofiber substrate by electrospinning technology, the electrospinning parameters include: an applied positive voltage of 10 kV-20 kV, an applied negative voltage of -1 kV to -5 kV, a drum speed of 400 rpm-600 rpm, a liquid supply rate of 0.02 mL / min-0.1 mL / min, a distance between the needle and the collecting device of 10 cm-20 cm, a temperature of 25° C.-35° C., and an ambient relative humidity of 35%-45%; (2) In the step of preparing the flexible nanofiber substrate by electrospinning technology, the mass volume ratio of the spinning solution used is 18%-26%, and the spinning solution is selected from a thermoplastic polyurethane solution and / or a styrene-butadiene-styrene block copolymer solution; (3) in the step of depositing the polyaniline sensitive layer on the first working part of the working electrode by cyclic voltammetry, using aniline solution as a raw material, and depositing the polyaniline sensitive layer on the first working part of the working electrode by cyclic voltammetry, wherein the concentration of aniline in the aniline solution is 0.1 mol / L-0.3 mol / L; (4) It also includes placing a protective layer precursor solution in the second working part of the reference electrode and forming a protective layer after drying, wherein the protective layer precursor solution includes polyvinyl butyral, sodium chloride, carbon nanotubes and an alcohol solvent, wherein the mass ratio of the polyvinyl butyral to the sodium chloride is 1.4:1-1.7:1, and the mass ratio of the polyvinyl butyral to the carbon nanotubes is 100:1-50:
1.
10. A flexible electrochemical pH sensor as claimed in any one of claims 1 to 5 for use in monitoring pH in body fluids.
Citation Information
Cited By
Miniaturized low-profile flexible ocean galvanic couple type pH sensor and preparation method thereof
CN120369791A
Flexible wearable long-term stable ruthenium oxide pH sensing electrode
CN120522252A
A flexible wearable long-term stable ruthenium oxide pH sensing electrode
CN120522252B
Miniaturized low-profile flexible ocean galvanic couple type pH sensor and preparation method thereof
CN121324459A
Miniaturized low profile flexible marine galvanic ph sensor and method of making same
CN121324459B